Prevalence and Mortality of Hypochloremia Among Patients with Coronary Artery Disease: A Cohort Study - Huang H; Mai Z; Chen L; Li Q; Chen S; Bao K; Tang R; Wei W; Yu Y; Huang Z; Lai W; Wang B; et al. (Dove Medical Press, 2021)
Haozhang Huang,1,2,* Ziling Mai,1,3,* Liling Chen,4,* Qiang Li,1 Shiqun Chen,1 Kunming Bao,4 Ronghui Tang,5 Wen Wei,4 Yaren Yu,6 Zhidong Huang,1 Wenguang Lai,1,3 Bo Wang,1 Ning Tan,1– 3 Jiyan Chen,1– 3 Jin Liu,1 Yong Liu1– 3 1Department of Cardiology, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Cardiovascular Institute, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People’s Republic of China; 2The Second School of Clinical Medicine, Southern Medical University, Guangzhou, 510515, People’s Republic of China; 3Guangdong General Hospital, Affiliated with South China University of Technology, Guangzhou, 510515, People’s Republic of China; 4Department of Cardiology, Longyan First Hospital Affiliated with Fujian Medical University, Longyan, 364000, People’s Republic of China; 5Yunnan Fuwai Cardiovascular Hospital, Department of Ultrasound Imaging, Yunnan, 650000, People’s Republic of China; 6The First People’s Hospital of Foshan, Foshan, Guangdong Province, 528000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong Liu; Jin LiuDepartment of Cardiology, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Cardiovascular Institute, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People’s Republic of ChinaTel +86 2083827812-10528Fax +86 2083851483Email liuyong@gdph.org.cn; ljaw397017568@163.comPurpose: Hypochloremia is a predictor for short-term mortality in patients with cardiovascular disease, but its association with coronary artery disease (CAD) is still unclear. We aimed to assess the impact of hypochloremia on all-cause mortality (short-and long-term) among patients with CAD.Patients and Methods: Based on the registry at Guangdong Provincial People’s Hospital in China, we analyzed data of 49,025 hospitalized patients who underwent coronary angiography (CAG) and were diagnosed with CAD from January 2007 to December 2018. To assess the association between hypochloremia and the study endpoints, a logistic-regression model (for 30-day all-cause mortality) and a Cox regression model (for long-term all-cause mortality) were fitted.Results: Overall, 4.4% of the study population showed hypochloremia (< 98 mmol/L). During a median follow-up of 5.2 (3.1– 7.8) years, a total of 6486 (13.2%) patients died. Patients with hypochloremia were generally older and at risk for diabetes, cardiorenal dysfunction, and morbidity than those without hypochloremia. After adjustment for confounders, hypochloremia remained a significant predictor of mortality risk (30-day all-cause death: adjusted odds ratio [aOR], 1.99; 95% confidence interval, 1.08– 3.18; P=0.017 and long-term all-cause death: adjusted hazard ratio [aHR], 1.32; 95% confidence interval, 1.19– 1.47; P< 0.001).Conclusion: Hypochloremia is mildly common in patients with CAD and is associated with increased short-and long-term mortality. Meanwhile, it is necessary to further investigate effective and preventive measures and the potential mechanisms of hypochloremia in patients with CAD.Keywords: hypochloremia, coronary artery disease, prevalence, short- and long-term mortality